Pratik Yangın Araştırması - Oduncu, Orhan (Sakarya Üniversitesi Yayınları, 2023)
Fire scene investigators examine the physical characteristics of a fire scene and identify and collect physical evidence at the scene. This evidence is then analyzed to help determine whether the cause of the fire was accidental or intentional. During the fire scene investigation, investigators may find evidence that could point to criminal activity, such as accelerants, damaged vehicles, and certain burn patterns. As a study aimed at developing new tools and techniques for interpreting, identifying, and analyzing evidence at the scene of a fire, this book will hopefully contribute to the improvement of fire research and help fill a gap in this field in our country.